Rise to the sun - Johnson, Leah (Young adult author) (Scholastic Press, 2021)
Three days. Two girls. One life-changing music festival. Toni is reeling in the wake of the loss of her roadie father and desperate to figure out where her life will go from here -- so she's heading back to the festival that taught her to love music in a last ditch effort to rediscover her passion. Olivia is a hopeless romantic whose heart has just taken a beating (again), and is beginning to believe that someone like her may never find "the one" -- but the Farmland Music and Arts Festival is a chance to at least find a place where she fits. When the two collide, it feels like kismet. But when something goes wrong and the festival is sent into a panic, Toni and Olivia find that they need each other, and the music, more than they ever imagined.